Menelisik Sejarah Penamaan Jalan Lubang Buaya dan Kaitannya dengan Peristiwa G30S - Aqiilah Afiifadiyah; Jumardi (Medan Resource Center, 2021)
This paper is a research on the history of naming Lubang Buaya using the interview method by examining the tomb of Mbah Prince Syarif bin Sheikh Abdul Rahman (Datok Flood) which is located on Jl. Kramat RT.7/RW.10, Lubang Buaya, Kec. Cipayung, East Jakarta City, which local residents believe is the person who coined the name Lubang Buaya. Then associate the name of Lubang Buaya with the G30S event. In fact, the naming of Lubang Buaya existed before the G30S event. There are two methods used in this paper, namely literature study and interviews (observation).